Masa depan Kecerdasan Buatan dalam Akuntansi Forensik - Muhammad Rizal; Rina Amelia; Yessica Amelia (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of artificial intelligence (AI) in forensic science has become an interesting topic and has brought tremendous progress in various fields, forensic science being one of them. With AI's ability to analyze large-scale data and detect patterns that are difficult for humans to see, this technology helps in speeding up investigations and increasing the accuracy of results. In the ever-growing digital era, the volume of data generated by organizations is increasingly large and complex. This creates significant challenges for forensic accountants in detecting and analyzing fraud and discrepancies in financial statements. AI offers innovative solutions with its ability to analyze large amounts of data, identify patterns, and detect anomalies at a speed and accuracy that far exceeds human capabilities.